The Bulgarian Revival in the memories about deeds and events of its builders: the Memoirs of Ekaterina Vassileva (Research Announcements "Heritage BG", 2025)
This publication presents an underknown woman figure of the Bulgarian National Revival. Ekaterina Vassileva belongs to two national traditions – the Romanian and the Bulgarian. Together with her husband Mihail Vassilev, she takes part in the establishment of the Bulgarian Literary Society in Braila. She writes in Romanian and in French. She is the author of memoirs, poems and articles and the prose poem ‘The Epic Bulgaria’ which she gives as a gift to the Russian emperor Alexander II in 1877, and to the Bulgarian prince Alexander I Battenberg in 1882.  References:Alexandrova 2012: Alexandrova, Nadezhda. Robini, kukli i chelovetsi. Predstavi za zhenite vav vazrozhdenskata publitsistika i v prozata na Lyuben Karavelov. Sofia, 83-87.Alexandrova 2019: Alexandrova, Nadezhda. Bilingvizmat i balgarskite avtorki ot 19 vek: Rakhil Dushanova, Ekaterina Vasileva, Bogdana Khiteva. – Literaturna misal, N 3, 57-72.Boycheva 1978: Boycheva, Kana. Aktrisite v emigrantskiya teatar na D. Voynikov. – Teatar, N 11, 43-45.Boycheva 1981: Boycheva, Kana. Ekaterina Vasileva. – Rodna rech, N 2, 51-53.Boycheva 2011: Boycheva, Kana. Zheni v syankata na izvestni mazhe. Sofia, 44-51.Ivancheva 1992: Ivancheva, Iren. Parvite balgarski poetesi. – Balgarska kniga, N 7, 42-46.Ivancheva 1995: Ivancheva, Iren. Bregove na chuvstvoto. Glasove na zheni v balgarskata poeziya. Sofia, 16.Karakostov 1973: Karakostov, Stefan. Balgarskiyat vazrozhdenski teatar na osvoboditelnata borba 1858-1878. Sofia, 491-496.Malinova 2012: Malinova, Lyudmila. Parvi predosvobozhdenski opiti na balgarkata v knizhovnostta i poeziyata. – Vezni, N 3, 46-61.Minchev 1957: Minchev, Dimitar. Neizvestni stranitsi za teatralnata deynost na Dobri Voynikov i Dimitar Veliksin. – Teatar, Х, 1957, N 11, 69-72.Minchev 1957: Minchev, Dimitar. Neizvestno stikhotvoreniye za Khadzhi Dimitar na rumanski ezik. – Vecherni novini, N 2165, 5 avgust 1958, p. 4.Paskaleva 1964: Paskaleva, Virdzhinia. Balgarkata prez Vazrazhdaneto. Sofia, 101-102, 146, 234, 245.Siupiur 1982: Siupiur, Elena. Balgarskata emigrantska inteligentsiya v Romaniya prez XIX vek. Sofia, 133-134, 157, 224.Zhechev 1970: Zhechev, Nikolay. Braila i balgarskoto kulturno-natsionalno vazrazhdane. Sofia, 110-111, 170-171, 180.